(untitled) - Hood, Philip (Los Angeles, 2015)
This second edition provides a coherent overview of teaching and learning languages, combining practical strategies for use in the classroom with engaging coverage of how to teach, informed by academic research and theory.
Keywords: Language and languages,Ngôn ngữ và ngôn ngữ; Study and teaching (Primary),Dạy và học (Tiểu học)